Analysis of the Green Economy Framework for the Sustainability of the Halal Industry in Indonesia - Sapinah Sapinah; Siradjuddin Siradjuddin; Murtiadi Awaluddin (Jurnal Ilmu Manajemen Profitability, 2026)
The halal industry is a strategic sector in Indonesia’s economy; however, its development continues to face sustainability challenges, particularly in integrating environmental considerations into the halal value chain. While the green economy paradigm has become central to sustainable development discourse, systematic efforts to integrate this framework within the Indonesian halal industry remain limited and fragmented. This study aims to analyze the systemic and conceptual integration of the green economy framework in supporting the sustainability of the halal industry in Indonesia.Using a qualitative approach, this research employs a narrative literature review of scientific articles indexed in Scopus, Web of Science, and Google Scholar from 2019–2025. Literature selection was conducted systematically based on thematic relevance, conceptual contribution, source quality, and contextual alignment with halal industry and green economy issues.The findings reveal that integrating green economy principles into the halal industry requires a multidimensional framework comprising five components: (1) green sharia value, (2) green production and clean technology, (3) sustainable halal supply chain, (4) green halal financing and investment, and (5) policy, governance, and public engagement. The model demonstrates that halal industry sustainability depends not only on sharia compliance but also on ecological efficiency, technological transformation, and collaborative governance. The study contributes theoretically by linking maqāṣid al-sharī‘ah with the green economy paradigm and provides practical guidance for developing sustainability-oriented national halal policies.